Survival time and related factors among child HIV/AIDS patients in Anhui province - Se-ying DAI; Ai-wen LIU; Lin JIN (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the survival time of child human immunodeficiency virus (HIV)/AIDS patients and its influencing factors in Anhui province. MethodsFollow-up and medication information on all laboratory confirmed AIDS patients aged ≤ 15 years at the diagnosis and being permanent residents of Anhui province were collected from National Comprehensive HIV/AIDS Information Management System up to the end of 2020 and analyzed retrospectively. The survival rate was calculated with life table method and impact factors of survival were assessed using Cox regression model. ResultsAmong a total of 329 child HIV/AIDS patients being followed-up during the period, 54 died of AIDS-related diseases and the mortality rate was 2.2/100 person-years. The results of Cox proportional hazards regression analysis showed that for all the child patients, the children with AIDS at the time of first diagnosis and not receiving antiretroviral therapy were at a significantly higher risk of AIDS-related disease mortality, with the hazard ratio (HR) of 5.32 (95% confidence interval [95% CI] : 2.70 - 10.47) and 28.29 (95% CI : 14.63 - 54.70) compared to those not having AIDS at the first diagnosis and to those receiving antiretroviral therapy; among the child patients with antiretroviral therapy, the risk of AIDS-related disease mortality were significantly higher for those aged < 5 years at the first diagnosis (versus aged 11 - 15 years: HR = 6.18, 95% CI : 14.63 - 54.70 ), having AIDS at the first diagnosis (versus having HIV infection: HR = 5.07, 95% CI : 1.27 - 20.29), and with the baseline CD4 + T lymphocyte count of < 50 cells/μL (HR = 10.99, 95% CI : 2.04 - 59.20) or 50 - 200 cells/μL (HR = 8.40, 95% CI : 1.35 - 52.26) compared to the child patients with the baseline count of > 200 cells/μL, respectively. ConclusionAmong child HIV/AIDS patients in Anhui province, antiretroviral therapy is an important factor for survival and the baseline CD4 + T lymphocyte count is the key factor affecting the effect of antiretroviral therapy.